2013
DOI: 10.1084/jem.20121674
|View full text |Cite
|
Sign up to set email alerts
|

p53 integrates host defense and cell fate during bacterial pneumonia

Abstract: p53 deletion augments neutrophil-mediated bacterial clearance in the lung at the expense of tissue homeostasis, leading to increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…For example, miR-33 was recently reported to repress the tumor suppressor p53 (50); we and others have reported that p53-deficient mice display enhanced proinflammatory gene expression in response to LPS due to derepression of NF-B (51,52). Alternatively, the potential for miR-33 to suppress inflammation in some contexts is also suggested by a recent report that miR-33 represses the NF-B co-activator receptor-interacting protein-140 (53).…”
Section: Mir-33 Regulates the Innate Immune Responsementioning
confidence: 84%
“…For example, miR-33 was recently reported to repress the tumor suppressor p53 (50); we and others have reported that p53-deficient mice display enhanced proinflammatory gene expression in response to LPS due to derepression of NF-B (51,52). Alternatively, the potential for miR-33 to suppress inflammation in some contexts is also suggested by a recent report that miR-33 represses the NF-B co-activator receptor-interacting protein-140 (53).…”
Section: Mir-33 Regulates the Innate Immune Responsementioning
confidence: 84%
“…The DNA damage responses orchestrated by ATM 17 and by p53 165 confer tissue damage control and disease tolerance to pulmonary bacterial infections in mice. Damage to cellular organelles in countered by the autophagy response.…”
Section: Box 3 Microbiota and Disease Tolerancementioning
confidence: 99%
“…Temperature and humidity of chamber air were monitored continuously, as was the O 3 concentration with a Teledyne T400 ultraviolet light photometer. BALF was collected immediately following sacrifice, and cell counts were performed as described previously (74). Protein analysis was performed using BCA protein assay (Pierce).…”
Section: Sterol Profiling Using Ptad Derivatization and Lc-selectedmentioning
confidence: 99%